2020
DOI: 10.12688/f1000research.20717.2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the addition of propolis to resin-modified glass ionomer cement bracket adhesive materials on the growth inhibition zone of Streptococcus mutans

Abstract: Background: Orthodontic treatments progress alongside the development of adhesive materials. The present study aimed to determine the antibacterial properties of propolis, a natural product, in a mixture of resin-modified glass ionomer cement by observing the growth inhibition zone of Streptococcus mutans. Methods: This was an in vitro study conducted on 45 samples of adhesive material, which were divided into control group (resin-modified glass ionomer cement bracket adhesive material), two groups of propolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These results met the clinical requirements of bond strength and did not inflict damage to the enamel surface. Recent studies have also shown that resin-modified glass ionomer adhesives can inhibit the growth of Streptococcus mutans and reduce demineralization [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results met the clinical requirements of bond strength and did not inflict damage to the enamel surface. Recent studies have also shown that resin-modified glass ionomer adhesives can inhibit the growth of Streptococcus mutans and reduce demineralization [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are polar compounds that have an antimicrobial response. 22 The other types of antibacterial contained in leaf plants that were extracted are eucalyptol in the eucalyptus leaf and eugenol in cinnamon leaf. The antibacterial substances of leaf and bark plants are different.…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of the COVID-19 pandemic in early 2020, the use of oral rinses or mouthwashes have been advised for orthodontic patient's due to the vulnerability of the virus to oxidation. Maintaining proper oral hygiene is difficult for these individuals; hence, efficient antibacterial agents, such as mouthwash, must be used to prevent the development of white spot lesions and stop the advancement of existing demineralization [11], [12]. However, mouthwashes include compounds that can influence orthodontic elastic force by altering the pH of the oral environment.…”
Section: Introductionmentioning
confidence: 99%